Determinants of Agricultural Extension Service Uptake by Smallholder Grape Farmers in Dodoma, Tanzania - Utonga, Dickson (Food, Agriculture and Natural Resources - NETWORKS, 2025)
Agricultural extension services are essential for enhancing smallholder farmers' productivity, promoting sustainability, and improving resilience in developing countries. However, socioeconomic, institutional, and technological challenges restrict the use of these services, despite their importance. In addition, the uptake of these services remains uneven in developing countries. This study examines the determinants of extension service uptake among smallholder grape farmers in Dodoma, Tanzania. Using a probit regression model on survey data from 120 small grape farmers, the analysis revealed significant factors influencing service uptake, including the farmer's gender, farming experience, and grape harvests. Male farmers were less likely to use extension services than their female counterparts, demonstrating gender barriers. The farming experience positively influenced the use of extension services, with more experienced farmers recognizing their benefits. In addition, higher harvests increased the likelihood of engagement, demonstrating that profitability motivates farmers to seek expert support. This study emphasizes on gender-sensitive interventions and outreach programs for inexperienced farmers, as well as improved access to extension services for low-harvest farmers. The interventions could bridge existing gaps, improve productivity, and unlock the economic potential of the grape sector.